Measurement of the absolute number of photons of the hard X‐ray beamline at the Linac Coherent Light Source. (11th February 2019) - Song, Sanghoon; Alonso-Mori, Roberto; Chollet, Matthieu; Feng, Yiping; Glownia, James M.; Lemke, Henrik T.; Sikorski, Marcin; Zhu, Diling; Moeller, Stefan; Lee, Hae Ja; Hunter, Mark S.; Carini, Gabriella; et al.
Abstract : Measurement of the absolute number of photons per pulse as a function of X‐ray photon energy at the hard X‐ray beamline of LCLS is presented. It is estimated by two different detectors and is used to characterize the hard X‐ray beamline optics transmission as well as the third‐harmonic content of the LCLS radiation. Abstract : X‐ray free‐electron lasers provide intense pulses of coherent X‐rays with a short pulse duration. These sources are chaotic by nature and therefore, to be used at their full potential, require that every X‐ray pulse is characterized in terms of various relevant properties such as intensity, photon energy, position and timing. Diagnostics are for example installed on an X‐ray beamline to specifically monitor the intensity of individual X‐ray pulses. To date, these can however only provide a single‐shot value of the relative number of photons per shot. Here are reported measurements made in January 2015 of the absolute number of photons in the hard X‐ray regime at LCLS which is typically 3.5 × 10 11 photons shot −1 between 6 and 9.5 keV at the X‐ray Pump–Probe instrument. Moreover, an average transmission of ≈62% of the hard X‐ray beamline over this energy range is measured and the third‐harmonic content of ≈0.47% below 9 keV is characterized.